STUDY INFORMATION SYSTEM SCHEDULING BASED ON PROCUREMENT OF GOODS IN CONNECTION WITH THE GOODS IN INVENTORY CONTROL PT. USI-JAYA - Sulwan Wahab; Drs. H. Soetirto Sadikin, M.A (Jurnal Sistem Informasi, 1990)
One of the major factors that support the production is the supply of goods, inaddition to the human / labor, machinery, and capital. Duty management arranged forthe above factors can work together to produce maximum output with minimuminput. Inventories of goods other than as one of the major factors that support theproduction also is one of asset / capital for the company, it was necessary to have auntu for inventory control, therefore it is necessary to have a control for theinventory.